Peningkatan Kualitas dan Kuantitas Hasil Tanaman Kacang Merah Menggunakan POC Darah Sapi Serta Pupuk Anorganik Sumber Nitrogen dan Sulfur - Maulana, Berlian Hafidzah; Astiningrum, Murti; Anindyawati, Nurul (Universitas Lampung, 2024)
This research was conducted to determine the effect of giving doses of liquid organic fertilizer cow's blood and inorganic fertilizers of the NPK Phonska and ZA on the quality and quantity of red bean plants (Phaseolus vulgaris L.). The research was carried out in August - October 2022 at the Kledung Research Park, Tidar University. The research method used a factorial experiment (4 x 2) with a complete group randomized design. The first factor is doses of cow blood liquid organic fertilizer consisting of 4 level: 0, 100, 200, 300 ml/plot 3,5 m2). The second factor was the addition of inorganic fertilizers with doses of NPK Phonska and ZA. The results of the analysis of this study showed that the application of liquid organic fertilizer cow blood at a dose of 160 - 240 ml/plot 3,5 m2 on red bean plants obtained the highest results on the number of pods planted, the weight of the pods planted, the number of seeds planted and the weight of seeds m2. The application of liquid organic fertilizer cow blood up to 300 ml/plot was able to increase yields on the wight of the seeds planted and the weight of Plant 100 seeds. The application of inorganic fertilizers of the NPK Phonska type gave higher results in number of pods per plant, weight of pods per plant, number of seeds per plant, weight of seeds/ m2 and weight of 100 seeds content compared with using ZA fertilizer. There was no interaction in the combined treatment of liquid organic cow blood fertilizer with inorganic fertilizers on all parameters. Keywords: Red bean, Cow blood liquid organic fertilizer, NPK Phonska, ZA